The two gentlemen of verona - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
The Two Gentlemen of Verona is a popular romantic comedy by the master playwright, William Shakespeare. It is believed to be his first comedy and probably his first play. It is about two inseparable friends, Valentine and Proteus, and how their friendship is affected when they fall in love. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play. It can also be used by teachers as a classroom resource
Keywords: Adaptations Juvenile literature